A Survey on Loanwords and Borrowings and Their Role in the Reflection of Cultural Values and Democracy Development: the Armenian Paradigm (European Journal of Marketing and Economics, 2022)
With the new wave of social sector becoming a fundamental element in generating and shaping democratic practices in such counties as Armenia, the role and the strategic prominence of language and loanwords has been highly reemphasized in the frames of thorough investigation of word borrowing practice and of its contribution to the egalitarian developments. The current paper aims at disclosing the essential dynamics in regard to the development of loanwords uncovered during a former field work in Armenia, which primarily concerns the process, the causes, the social dynamics through which loanwords emerge, as well as the issues of "purity" of vocabulary and the interconnection between loanwords and local development processes in Armenia. The article is based on qualitative research methods; semi-structured, focus group and informal interviews have been carried out in order to collect the needed data. The results of the article suggest that being the basis of communication among different countries and societies, the process of word borrowing however is not always easy and autonomous, especially in the scope of democracy building; the creation and the development of new words and concepts is a complicated task, which requires cultural exchange, real manifestation of the concepts induced, as well as apt and professional assistance and sustenance. The paper concludes that notwithstanding all the efforts by humans, geopolitical, economic and cultural forces play a significantly stronger role, and thus changes and modifications in a language are inevitable, moreover the process appeals for facilitation and support in such developing countries as Armenia.
Keywords: sociolinguistics, localization of English, loanwords, neologisms in democracy building, local development in English